2013
DOI: 10.1038/ncomms2922
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol transmission is an important mode of influenza A virus spread

Abstract: Influenza A viruses are believed to spread between humans through contact, large respiratory droplets and small particle droplet nuclei (aerosols), but the relative importance of each of these modes of transmission is unclear. Volunteer studies suggest that infections via aerosol transmission may have a higher risk of febrile illness. Here we apply a mathematical model to data from randomized controlled trials of hand hygiene and surgical face masks in Hong Kong and Bangkok households. In these particular envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
254
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(288 citation statements)
references
References 33 publications
8
254
2
3
Order By: Relevance
“…In this study, we refined our previous findings on 59 confirmed infections [7] with a much larger number of cases from 7 years of recruitment, including also cases infected with influenza A(H1N1)pdm09 virus. Although secondary cases in a household setting might not be representative of all natural influenza infections in other community settings because of the particular mechanisms of transmission in households [17], it has been estimated that a large proportion of community disease transmission does take place in the household setting [18]. In a subset of these households, we used viral genetic sequences to demonstrate that >95% of the infections among household contacts did occur within the household [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we refined our previous findings on 59 confirmed infections [7] with a much larger number of cases from 7 years of recruitment, including also cases infected with influenza A(H1N1)pdm09 virus. Although secondary cases in a household setting might not be representative of all natural influenza infections in other community settings because of the particular mechanisms of transmission in households [17], it has been estimated that a large proportion of community disease transmission does take place in the household setting [18]. In a subset of these households, we used viral genetic sequences to demonstrate that >95% of the infections among household contacts did occur within the household [19].…”
Section: Discussionmentioning
confidence: 99%
“…How best to associate symptoms to transmission potential remains an open question. For instance, while sneezing likely helps transmission in both humans and ferrets, there does not seem an easy and general relation between the two, with different mechanisms of transmission all contributing [79][80][81][82].…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…Natural infections are initiated primarily through direct and indirect contact with virus-coated surfaces, or through inhalation of virus-bearing respiratory droplets [9799]. Regardless of route, the transmission dose of IAV is thought to generally be low.…”
Section: How ‘Noninfectious’ Particles Might Contribute To Infectionmentioning
confidence: 99%